Recent Advances in High-Entropy Alloys for Electrocatalysis: From Rational Design to Functional Performance - Zagal-Moya, J; Zagal-Moya, J; Azocar-Guzman, M; Azocar-Guzman, M; Jimenez-Arevalo, V; Jimenez-Arevalo, V (Elsevier Ltd, 2025)
High-entropy alloys (HEAs) represent a transformative class of materials for electrocatalysis, challenging conventional alloy design by incorporating five or more principal elements into single- or multiphase solid solutions. This compositional complexity enables exceptional tunability of electronic structures, adsorption energies, and catalytic behavior. HEAs offer a promising route to overcome the limitations of noble-metal-based catalysts, such as high cost, limited availability, and poor long-term stability. This review critically evaluates recent advances in the design, synthesis, and electrochemical performance of HEAs across key electrocatalytic reactions, including the hydrogen evolution reaction (HER), oxygen evolution (OER), oxygen reduction (ORR), methanol and ethanol oxidation (MOR and EOR), carbon dioxide reduction (CO2RR), and nitrogen reduction (NRR). Emphasis is placed on the synergistic effects, hybridization of orbitales in HEAs, configurational entropy contributions, and defect-rich surfaces that collectively enhance catalytic activity and durability. We highlight emerging synthetic strategies, such as thermal shock, solvothermal methods, and dealloying, that enable controlled fabrication of HEA nanostructures with optimized properties. In parallel, we examine computational and data-driven approaches, including semi-empirical models, CALPHAD, first-principles simulations, and AI-based frameworks, that facilitate rational design and accelerated discovery. Finally, we outline current challenges and future directions toward scalable production, stability under realistic conditions, and integration into sustainable energy systems. © 2025 The Author(s)